Implikasi Pola Makan Tinggi Natrium Terhadap Kejadian Hipertensi di Masyarakat Pesisir - Prasetyowati, Irma; Puspitasari, Muthia Fahriyah; Putri, Syafira Aurellia; Ayunni, Kartika Astri Firda; Thoyiba, Nuzula Lailatul; Hilmiy, Daryta Balqis Nashifa; Nurmusfiroh, Rizqi Faza; Zahro, Adinda Khatimatuz; Salsabilah, Della Estelina; Wijaya, Novita Dian Rahmawati (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background: Hypertension, commonly referred to as